Textured PbZr0.3Ti0.7O3 thin films produced by polymeric precursor method using microwave oven - Escote, M. T.; Pontes, F. M.; Leite, E. R.; Longo, Elson [UNESP] (Taylor & Francis Ltd, 2006)
PbZr0.3Ti0.7O3 (PZT) films were produced by polymeric precursor route and deposited by spin-coater technique on Pt(111)/Ti/SiO2/Si(100) substrates. The films were heat-treated using different furnaces: (a) a conventional furnace, at 700 degrees C; and (b) a domestic microwave oven, at 600 degrees C. The X-ray patterns revealed that both films are single phase and reflections were identified as belongs to the PZT phase. The intensity of these reflections showed a (111), (001) and (100) preferred orientation. Morphological and electrical characterizations showed that all samples present a rather different microstructure and both with high spontaneous polarization.
Keywords: ferroelectric; film; polymeric precursor route; PZT; microwave oven